Effect of feeding cottonseed cake on male fertility in rabbit - Kenfack, A; Chombong, JK; Ngoula, F; Vemo, NB; Tsambou, AMM; Zeukeng, GMZ; Mama, B; Tchoumboué, J (Bangladesh Journal of Animal Science, 2015)
In order to study the effects of cottonseed cake on the fertility of the male rabbit, 60 animals (40 bucks and 20 does) were used. Males were 3 months old at the beginning of the essay, and the females were multiparous. Males were divided into 4 identical groups. Four diets containing 0, 6, 12 and 18% of cottonseed cake were formulated and randomly allotted to different groups of males. All the females received the same diet (6%). The treatment lasted for 90 days. At the end of that period, 5 males were sacrificed per lot and the rest were allowed to mate each with an untreated female before being sacrificed in turn. No significant difference (p>0.05) was observed among rations for the volume of testis and weight of reproductive organs. Histological study of the testes revealed no abnormality. In the presence of an untreated female, hundred percent of rabbits realized mounting and ejaculated whichever the cottonseed cake level. Nevertheless, the volume of the ejaculate was significantly (p>0.05) low in rabbit fed 6% cottonseed cake (0.86 vs 1.66, 12%). The spermatozoa concentration in the cauda epididymis was higher in rabbit given cottonseed cake than in control, although not significantly (p>0.05). The adverse effects of the toxicant contained in cottonseed cake occurred at 18% inclusion. The result showed that it is not possible to generalize the upper limit of inclusion of cottonseed cake in the ration formulation. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23123 Bang. J. Anim. Sci. 2014. 44 (1): 16-20